Il programma VEGA ad una svolta - Michele Dussi (GEOmedia, 2008)
VEGA is an ESA program to develop a small European launcher (VEGA) stands for Vettore Europeo di Generazione Avanzata – Advanced Generation European Launcher) primarily based on Italian industrial activities and funds. VEGA is able to put a payload of 1,5 tons in a 700 km orbit. During the next months the third stage booster will be submitted to final qualification test. Then the maiden launch will be scheduled for the last quarter of 2009.